While we were planning: Unexpected developments in international politics. Foresight contributions 2018 - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2018)
How might we have to imagine the Middle East if there were a political thaw between Iran and Saudi Arabia? Could Turkey leave NATO in the near future? What would happen if security-related EU databases were successfully hacked; if South Korea were to arm itself with nuclear weapons; or if an American woman were to head the United Nations? Of course, these situations, as explored in the SWP's latest Foresight research paper, are only hypothetical. Why address them? Because unexpected events have abounded in international politics in recent years. Brexit; the election of Donald Trump as US President; and Russia's annexation of Crimea are only the most striking examples. Science and politics should therefore ready themselves for likely future surprises. The Foresight research paper aims to assist with this. We cannot and do not want to predict the future. However, with the help of systematic foresight we can better prepare for unplanned situations. This means improving our view of conceivable - albeit unlikely - developments that would seriously impact on German and European foreign and security policy. It also includes reviewing previous expectations - as this research paper likewise tackles. What actually happened to the battery revolution that was supposed to secure our power supply? Did the negotiation process on the UK's withdrawal from the EU unfold as experts had anticipated? Such reviews are instructive, and can be used to gain insights for the future.
Keywords: 320